Preparation method of turnover type multifunctional terahertz electromagnetic shielding composite material
Modal cotton conductive fabric doped with nickel-coated carbon powder is prepared by combining autocatalytic electroless plating and dip coating, and a hybrid network structure is formed with graphite conductive glue, which solves the shortcomings of multi-band electromagnetic shielding materials in the prior art, and achieves efficient electromagnetic shielding and versatility. It is suitable for electromagnetic protection and electromagnetic compatibility in 5G and 6G technologies.
Patent Information
- Application Number
- CN202411743114.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-14
AI Technical Summary
It is difficult for the prior art to develop multifunctional materials that have both multi-band electromagnetic shielding capabilities and other functions, especially in terms of electromagnetic protection and electromagnetic compatibility in 5G and 6G technologies.
Through a series of surface grafting methods combined with autocatalytic electroless plating and dip coating, modal cotton conductive fabrics doped with nickel-coated carbon powder (Ni/CP) were prepared, and a hybrid network structure was formed with graphite conductive glue, which improved electromagnetic shielding efficiency and had multifunctional characteristics such as strain sensing and Joule heating.
It realizes efficient electromagnetic shielding performance in the GHz band and the THz band, with the average shielding efficiency reaching 41.65~42.88 dB and 45.93~48.63 dB respectively, and is versatile, suitable for electromagnetic protection and electromagnetic compatibility in 5G and 6G technologies.
Smart Images

Figure CN119615610A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electronic materials, and in particular relates to a method for preparing a flip-type multifunctional terahertz electromagnetic shielding composite material. Background Art
[0002] With the development of artificial intelligence and advanced communication technology, smart wearable electronic devices have shown broad application prospects in many fields such as human body monitoring, intelligent display, human-computer interaction and wireless communication. The development and widespread use of electronic devices have significantly improved people's quality of life. However, the electromagnetic wave interference and radiation generated in an increasingly complex environment pose a major threat to human health and the normal operation of the equipment itself. At present, the development of 5G communication technology is booming around the world, and 6G communication technology, especially terahertz (THz) transmission technology, is also receiving more and more attention. In this case, the demand for multi-band electromagnetic shielding materials has further increased. In addition, with the substantial increase in the complexity of application scenarios and environments, the versatility of smart wearable materials has become one of the current development trends. The integration of multiple functions can further meet the needs of lightweight and comfort. Therefore, it is urgent to design multifunctional materials that have both multi-band electromagnetic shielding capabilities and other functions.
[0003] To address this challenge, flexible fabrics have become one of the most promising choices for substrates of smart wearable devices due to their low cost and flexibility. Flexible fabrics have inherent mechanical flexibility, low density, high specific surface area (convenient for fixing active materials), and unique porous fiber network structure. In addition, it is worth noting that fabric-based smart wearable devices can be integrated with clothing to the greatest extent, making clothing intelligent while maintaining its original breathability, flexibility, and environmental stability.
[0004] Currently, carbon-based conductive materials and metal powder materials are two widely used materials for preparing flexible conductive fabrics with high electromagnetic shielding effectiveness. Such fillers can be combined with the network skeleton of the fabric to construct an effective conductive path. In contrast, the density and price of metal powder materials are much higher. In addition, the network skeleton constructed by metal powder is rigid and brittle, and is easily oxidized in the air. Therefore, carbon-based conductive materials with good electrical and thermal conductivity, excellent high temperature resistance and chemical stability, such as carbon black (CB) (Z. Liu, X. Gao, B. Zhu, X. Yuan, Sea urchin-like MnO2@Carbon fiber paper @carbon black modifiedsilicone rubber interface control to improve electromagnetic properties and media factors, Chem. Eng. J. 495 (2024) 153528;A. Rajan, S. K Solaman, S. Ganesanpotti, Design and Fabrication of Layered Electromagnetic Interference Shielding Materials: A Cost-Effective Strategy for Performance Prediction andEfficiency Tuning, ACS Applied Materials & Interfaces 15(4) (2023) 5822-5835.), carbon nanotubes (CNTs) (Q.-D. Nguyen, Y. Yi, C.-G. Choi, Highly conductive carbon nanotubes-boron nitride-thermoplastic polyurethanecomposite thin films with ultra broadband and efficient electromagnetic interference shielding up to 110 GHz and heat dissipation abilities, Materials Today Physics 44 (2024) 101430; H. Liu, X.Zhang, K. Li, Qa Cui, L. Han, Q. Shen, H. Li, X. Yin, Construction of core-shell structured SiCnanowires@carbon nanotubes hybrid conductive network for supercapacitors and electromagnetic interference shielding, Carbon 228 (2024) 119411.) and graphene (Z. Wang, G. Cai, Y. Xia, P. Li, S. Shi, B. Wang, W. Gao, Y. Liu,Z. Xu, C. Gao, Highly conductive graphene fiber textile for electromagnetic interference shielding, Carbon 222 (2024) 118996; N. Luo, Y.-y. Zhang, H.Zhang, T.-l. Liu, Y. Wang, F. Chen, Q. Fu, Electromagnetic interferenceshielding performance of lightweight aramid nanofiber / graphene compositeaerogels, Journal of Materials Chemistry A 12(17) (2024) 10359-10368.), has been widely used as a filler component in polymers to replace metal powder materials. Zheng et al. prepared rGO / Ti by a simple dip-spray coating method. 3 C 2 T xModified cotton fabric (X. Zheng, W. Nie, Q. Hu, X. Wang, Z. Wang, L.Zou, X. Hong, H. Yang, J. Shen, C. Li, Multifunctional RGO / Ti3C2Tx MXenefabrics for electrochemical energy storage, electromagnetic interference shielding, electrothermal and human motion detection, Materials & Design 200(2021) 109442.). The prepared composite material exhibits low surface resistance (13.8 Ω / □), good electrical conductivity (high specific capacitance of 383.3 F g -1 ), EMI shielding performance of 29.04 dB in the X-band, and Joule heating characteristics. However, carbon-based conductive materials still have certain limitations. The uniform distribution of conductive materials on the fabric network skeleton is a prerequisite for the preparation of stable conductive coatings, but carbon-based materials tend to accumulate in the skeleton. To solve this problem, a mixed conductive system can be formed by modifying carbon materials or adding other modifiers, thereby improving the uniformity of conductive fillers and enhancing conductive properties.
[0005] Xie et al. demonstrated a simple spraying method (C. Xie, Y. Wang, W. Wang, D. Yu, Flexible, conductive and multifunctional cotton fabric with surface wrinkledMXene / CNTs microstructure for electromagnetic interference shielding, Colloids and Surfaces A: Physicochemical and Engineering Aspects 651 (2022) 129713.) to construct conductive fabrics with wrinkled microstructures on cotton knitted fabrics by using one-dimensional carbon nanotubes (CNTs) as the skeleton and two-dimensional MXene as the stacking layer. These fabrics exhibited efficient EMI shielding performance (46.05 dB) and good Joule heating performance. However, as an emerging material, the high cost of MXene significantly limits the possibility of these fabrics in large-scale practical applications. In addition, a simpler but equally effective method is needed to prepare conductive fabrics.
[0006] The present invention proposes an economical and efficient method of preparing modal cotton conductive fabric doped with nickel-coated carbon powder (Ni / CP) by combining self-catalytic chemical plating and dip coating with a series of surface grafting. Ni / CP material combines the advantages of metal materials and carbon-based materials. In the prepared conductive fabric, the hybrid network structure formed with graphite conductive glue significantly improves the electromagnetic shielding efficiency. The average shielding effectiveness in the ultra-high frequency (UHF) band, X-band and terahertz (THz) band reaches 41.65~42.88 dB, 35.90~38.31 dB, and 45.93~48.63 dB, respectively. It also has multifunctional properties such as strain sensing and Joule heating. The prepared flip-type multifunctional terahertz electromagnetic shielding composite material shows great application potential in wearable electronic devices and multifunctional, multi-band EMI shielding scenarios.
[0007] According to the electromagnetic shielding effectiveness calculation formula, the reflection efficiency SE R = -10×log10(1-R), where R is the reflectivity, and SE is the reflectivity. R >3.0103 dB, then R>50%, that is, the shielding mechanism of the material is mainly reflection loss. The flip performance of the composite material of the present invention is: in the GHz frequency band, it is a shielding material mainly based on reflection loss (SE R >5 dB, while in the THz frequency band (0.8~2.0 THz), it turns into a shielding material with absorption loss as the main factor (SE R <3 dB), i.e., a reversal of the shielding mechanism has occurred. Summary of the invention
[0008] The purpose of the present invention is to propose a method for preparing a flip-type multifunctional terahertz electromagnetic shielding composite material, to provide new materials for electromagnetic protection and electromagnetic compatibility of 5G and 6G technologies, while having wearable mechanical sensing and Joule heating properties, to achieve the multifunctionality of a single material.
[0009] The method for preparing the flip-type multifunctional terahertz electromagnetic shielding composite material proposed in the present invention is characterized by: (1) Carbon powder modification: immerse carbon powder with an average particle size of 10-13 μm in an aqueous solution of 3-aminopropyltriethoxysilane with a mass percentage concentration of 5-10%, stir, heat to 30-40°C and react for 2-4 hours, filter, rinse with water, and dry to obtain modified carbon powder; (2) Catalytic activation: Place the modified carbon powder in a 1-3% mass percent palladium chloride aqueous solution, stir at room temperature for 1-3 h, filter, and then disperse the solid in a 1-3% mass percent 2-aminopyridine aqueous solution, stir at room temperature for 1-3 h, filter, rinse the solid with water, and dry to obtain activated carbon powder; (3) Chemical nickel plating: Place the activated carbon powder in a chemical nickel plating solution, place it at 70-80°C for 3-5 minutes, take it out, rinse it with water, and dry it to obtain nickel-coated carbon powder; wherein the components and concentrations of the chemical nickel plating solution are: NiCl 2 6H 2 O: 50~60 g / L, NaKC 4 H 4 O 6 :70~80 g / L, NaH 2 PO 2 ·2H 2 O: 25~30g / L, NH 3 ·H 2 O: 50~60 g / L, the rest is deionized water; (4) Slurry preparation: Mix the nickel-coated carbon powder with a graphite conductive adhesive having a solid content of 2-4%, and stir for 1-2 hours to obtain a composite slurry; wherein the mass ratio of the nickel-coated carbon powder to the graphite conductive adhesive is 0.01-0.10; (5) Coating and molding: prepare two square plastic molds with a height of 0.35 mm and a side length of 16 cm. First, pour the composite slurry into one mold and fill it up. Use a scraper to scrape off the excess composite slurry. Then, lay the modal cotton fabric cut into 15 cm × 15 cm flat on the slurry to ensure that the fabric is in full contact with the slurry. Then, place the second mold on the first mold and align the four sides. Then, pour the composite slurry on the modal cotton fabric in the mold and fill it up. Use a scraper to scrape off the excess composite slurry. Place it at room temperature for 24 hours, demold it, place it in an oven, heat it to 30~45℃, and keep it for 3~5 hours to obtain a flip-type multifunctional terahertz electromagnetic shielding composite material.
[0010] The electromagnetic shielding performance tests of the composite material are: (1) The electromagnetic shielding effectiveness in the frequency range of 0.3~3.0 GHz was tested by a vector network analyzer using the coaxial transmission line method. The average electromagnetic shielding effectiveness was 41.65~42.88 dB. (2) The electromagnetic shielding performance and S parameters in the frequency range of 8.2~12.4 GHz were tested by vector network analyzer using the waveguide method. The average electromagnetic shielding effectiveness was 35.90~38.31 dB. (3) The electromagnetic shielding effectiveness in the frequency range of 0.2~2.0 THz was tested using a terahertz time-domain spectroscopy (THz-TDS) system in transmission mode and reflection mode. The average electromagnetic shielding effectiveness was 45.93~48.63 dB.
[0011] The mechanical sensing performance test of the composite material is to use an electronic tensile testing machine to measure the stress-strain curve, and use an LCR tester to characterize the resistance change of the composite material during the stretching process. The tensile strain sensitivity of the composite material is measured to be 2500~2897.
[0012] The Joule heating performance test of the composite material is carried out by monitoring the real-time temperature change of the composite material surface at room temperature using an infrared thermometer. It is measured that under a voltage of 10V and an action of 600 seconds, the average surface temperature of the composite material is 120~126℃.
[0013] The present invention has the following advantages: (1) Multifunctionality: providing new materials for electromagnetic protection and electromagnetic compatibility of 5G and 6G technologies, while also having wearable mechanical sensing and Joule heating performance; (2) Unique shielding performance. In the GHz frequency band, it is a shielding material with reflection loss as the main factor (SE R >5 dB, while in the THz frequency band (0.8~2.0 THz), it turns into a shielding material with absorption loss as the main factor (SE R <3 dB), see the attached Figure 2 , Attachment Figure 3 , where SE T is the total shielding effectiveness, SE A is the wave absorbing efficiency, SE R is the reflection efficiency, SE T = SE A +SE R ; (3) Used in the field of electromagnetic safety protection of 6G technology, due to its low reflectivity, it can avoid interference from secondary reflection of electromagnetic waves.
[0014] Invention patent CN202310836051.7 discloses a polymer-based electromagnetic shielding material with shielding effectiveness in the GHz to THz band, and its preparation method and application, including: adding a gel matrix to a PEDOT:PSS aqueous solution, stirring and mixing, and then standing; subjecting the products after standing to freeze-thaw cycles and freeze-drying, respectively, to obtain a polymer-based electromagnetic shielding material with shielding effectiveness in the GHz to THz band. The invention also discloses a polymer-based electromagnetic shielding material with shielding effectiveness in the GHz to THz band prepared by the above-mentioned preparation method. The preparation method of the invention is simple, and the prepared polymer-based electromagnetic shielding material has dual-scale closed micropores and a staggered layered structure, which can produce multiple reflections, expand the electromagnetic wave shielding bandwidth, and improve the electromagnetic shielding effectiveness. It has broad application prospects in the anti-electromagnetic interference and electromagnetic compatibility design in the field of 5G and even 6G technology. The invention has a different material system and preparation method from the present invention. The material prepared by the invention is not multifunctional, and it is not clear whether it is a reflection loss type or an absorption loss type, which is different from the mechanism of action of the present invention.
[0015] Invention patent CN201780097309.9 discloses the application of polymer-carbon materials for shielding electromagnetic radiation with wavelengths in the sub-terahertz and terahertz ranges, wherein in a matrix of a non-conductive thermoplastic polymer, elastomer or silicone, a filler is dispersed in the form of a carbon nanostructure in an amount of 0.1%wt to 10%wt, for selectively shielding radiation in the range of 0.1THz to 10THz, with an efficiency exceeding 10dB in at least a portion of the mentioned sub-terahertz range, and a composite material obtained by direct mixing and curing of a fluid polymer and a filler is used, and the composite material used is non-conductive to direct current. The invention has a different material system and preparation method from the present invention, and the material prepared by the present invention has higher wave absorption efficiency, multi-band electromagnetic protection efficiency, and multifunctionality, which are not available in CN201780097309.9. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a scanning electron microscope photograph of the flip-type multifunctional terahertz electromagnetic shielding composite material.
[0017] Figure 2 This is a test diagram of the electromagnetic shielding effectiveness of the flip-type multifunctional terahertz electromagnetic shielding composite material in the THz frequency band.
[0018] Figure 3 This is a test chart of the electromagnetic shielding effectiveness of the flip-type multifunctional terahertz electromagnetic shielding composite material in the GHz frequency band. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. Example 1
[0020] (1) Carbon powder modification: Immerse carbon powder with an average particle size of 10 μm in an aqueous solution of 3-aminopropyltriethoxysilane with a mass percentage concentration of 5%, stir, heat to 30°C and react for 2 hours, filter, rinse with water, and dry to obtain modified carbon powder; (2) Catalytic activation: Place the modified carbon powder in a 1% mass percent palladium chloride aqueous solution, stir at room temperature for 1 hour, filter, and then disperse the solid in a 1% mass percent 2-aminopyridine aqueous solution, stir at room temperature for 1 hour, filter, rinse the solid with water, and dry to obtain activated carbon powder; (3) Chemical nickel plating: The activated carbon powder is placed in a chemical nickel plating solution, placed at 70°C for 3 minutes, taken out, rinsed with water, and dried to obtain nickel-coated carbon powder; wherein the components and concentrations of the chemical nickel plating solution are: NiCl 2 6H 2 O: 50g / L, NaKC 4 H 4 O 6 :70 g / L,NaH 2 PO 2 ·2H 2 O: 25g / L, NH 3 ·H 2 O: 50 g / L, the balance is deionized water; (4) Slurry preparation: Mix the nickel-coated carbon powder with a graphite conductive adhesive having a solid content of 2% and stir for 1 hour to obtain a composite slurry; wherein the mass ratio of the nickel-coated carbon powder to the graphite conductive adhesive is 0.01; (5) Coating and molding: prepare two square plastic molds with a height of 0.35 mm and a side length of 16 cm. First, pour the composite slurry into one mold and fill it up. Use a scraper to scrape off the excess composite slurry. Then, lay the modal cotton fabric cut into 15 cm × 15 cm flat on the slurry to ensure that the fabric is in full contact with the slurry. Then, place the second mold on the first mold and align the four sides. Then, pour the composite slurry on the modal cotton fabric in the mold and fill it up. Use a scraper to scrape off the excess composite slurry. Place it at room temperature for 24 hours, demold it, place it in an oven, heat it to 30°C, and keep it for 3 hours to obtain a flip-type multifunctional terahertz electromagnetic shielding composite material.
[0021] The electromagnetic shielding performance tests of the composite material are: (1) The electromagnetic shielding effectiveness in the frequency range of 0.3~3.0 GHz was tested by a vector network analyzer using the coaxial transmission line method. The average electromagnetic shielding effectiveness was 41.65 dB. (2) The electromagnetic shielding performance and S parameters in the frequency range of 8.2~12.4 GHz were tested by vector network analyzer using the waveguide method. The average electromagnetic shielding effectiveness was 35.90 dB. (3) The electromagnetic shielding effectiveness in the frequency range of 0.2~2.0 THz was tested using a terahertz time-domain spectroscopy (THz-TDS) system in transmission mode and reflection mode. The average electromagnetic shielding effectiveness was 45.93 dB.
[0022] The mechanical sensing performance test of the composite material is to use an electronic tensile testing machine to measure the stress-strain curve, and use an LCR tester to characterize the resistance change of the composite material during the stretching process. The tensile strain sensitivity of the composite material is measured to be 2897.
[0023] The Joule heating performance test of the composite material is carried out by monitoring the real-time temperature change of the composite material surface at room temperature using an infrared thermometer. It is measured that under a voltage of 10V and an action of 600 seconds, the average surface temperature of the composite material is 120°C. Example 2
[0024] (1) Carbon powder modification: Immerse carbon powder with an average particle size of 13 μm in an aqueous solution of 3-aminopropyltriethoxysilane with a mass percentage concentration of 10%, stir, heat to 40°C for reaction for 4 hours, filter, rinse with water, and dry to obtain modified carbon powder; (2) Catalytic activation: Place the modified carbon powder in a 3% by mass concentration of palladium chloride aqueous solution, stir at room temperature for 3 hours, filter, and then disperse the solid in a 3% by mass concentration of 2-aminopyridine aqueous solution, stir at room temperature for 3 hours, filter, rinse the solid with water, and dry to obtain activated carbon powder; (3) Chemical nickel plating: The activated carbon powder is placed in a chemical nickel plating solution, placed at 80°C for 5 minutes, taken out, rinsed with water, and dried to obtain nickel-coated carbon powder; wherein the components and concentrations of the chemical nickel plating solution are: NiCl 2 6H 2 O: 60 g / L, NaKC 4 H 4 O 6 :80 g / L,NaH 2 PO 2 ·2H 2 O: 30g / L, NH 3 ·H 2 O: 60 g / L, the balance is deionized water; (4) Slurry preparation: Mix nickel-coated carbon powder and graphite conductive glue with a solid content of 4%, and stir for 2 hours to obtain a composite slurry; wherein the mass ratio of nickel-coated carbon powder to graphite conductive glue is 0.10; (5) Coating and molding: prepare two square plastic molds with a height of 0.35 mm and a side length of 16 cm. First, pour the composite slurry into one mold and fill it up. Use a scraper to scrape off the excess composite slurry. Then, lay the modal cotton fabric cut into 15 cm × 15 cm flat on the slurry to ensure that the fabric is in full contact with the slurry. Then, place the second mold on the first mold and align the four sides. Then, pour the composite slurry on the modal cotton fabric in the mold and fill it up. Use a scraper to scrape off the excess composite slurry. Place it at room temperature for 24 hours, demold it, place it in an oven, heat it to 45°C, and keep it for 5 hours to obtain a flip-type multifunctional terahertz electromagnetic shielding composite material.
[0025] The electromagnetic shielding performance tests of the composite material are: (1) The electromagnetic shielding effectiveness in the frequency range of 0.3~3.0 GHz was tested by a vector network analyzer using the coaxial transmission line method. The average electromagnetic shielding effectiveness was 42.88 dB. (2) The electromagnetic shielding performance and S parameters in the frequency range of 8.2~12.4 GHz were tested by vector network analyzer using the waveguide method. The average electromagnetic shielding effectiveness was 38.31 dB. (3) The electromagnetic shielding effectiveness in the frequency range of 0.2~2.0 THz was tested using a terahertz time-domain spectroscopy (THz-TDS) system in transmission mode and reflection mode. The average electromagnetic shielding effectiveness was 48.63 dB.
[0026] The mechanical sensing performance test of the composite material is to use an electronic tensile testing machine to measure the stress-strain curve, and use an LCR tester to characterize the resistance change of the composite material during the stretching process. The tensile strain sensitivity of the composite material is measured to be 2500.
[0027] The Joule heating performance test of the composite material is carried out by monitoring the real-time temperature change of the composite material surface at room temperature using an infrared thermometer. It is measured that under a voltage of 10V and an action of 600 seconds, the average surface temperature of the composite material is 126°C. Example 3
[0028] (1) Carbon powder modification: Immerse carbon powder with an average particle size of 10 μm in an aqueous solution of 3-aminopropyltriethoxysilane with a mass percentage concentration of 10%, stir, heat to 30°C and react for 4 hours, filter, rinse with water, and dry to obtain modified carbon powder; (2) Catalytic activation: Place the modified carbon powder in a 1% by mass concentration of palladium chloride aqueous solution, stir at room temperature for 3 hours, filter, and then disperse the solid in a 1% by mass concentration of 2-aminopyridine aqueous solution, stir at room temperature for 3 hours, filter, rinse the solid with water, and dry to obtain activated carbon powder; (3) Chemical nickel plating: The activated carbon powder is placed in a chemical nickel plating solution, placed at 70°C for 5 minutes, taken out, rinsed with water, and dried to obtain nickel-coated carbon powder; wherein the components and concentrations of the chemical nickel plating solution are: NiCl 2 6H 2 O: 50 g / L, NaKC 4 H 4 O 6 : 80 g / L, NaH 2 PO 2 ·2H 2 O: 25g / L, NH 3 ·H 2 O: 60 g / L, the balance is deionized water; (4) Slurry preparation: Mix nickel-coated carbon powder and graphite conductive glue with a solid content of 2%, and stir for 2 hours to obtain a composite slurry; wherein the mass ratio of nickel-coated carbon powder to graphite conductive glue is 0.05; (5) Coating and molding: prepare two square plastic molds with a height of 0.35 mm and a side length of 16 cm. First, pour the composite slurry into one mold and fill it up. Use a scraper to scrape off the excess composite slurry. Then, lay the modal cotton fabric cut into 15 cm × 15 cm flat on the slurry to ensure that the fabric is in full contact with the slurry. Then, place the second mold on the first mold and align the four sides. Then, pour the composite slurry on the modal cotton fabric in the mold and fill it up. Use a scraper to scrape off the excess composite slurry. Place it at room temperature for 24 hours, demold it, place it in an oven, heat it to 30°C, and keep it for 5 hours to obtain a flip-type multifunctional terahertz electromagnetic shielding composite material.
[0029] The electromagnetic shielding performance tests of the composite material are: (1) The electromagnetic shielding effectiveness in the frequency range of 0.3~3.0 GHz was tested by a vector network analyzer using the coaxial transmission line method. The average electromagnetic shielding effectiveness was 41.98 dB. (2) The electromagnetic shielding performance and S parameters in the frequency range of 8.2~12.4 GHz were tested by vector network analyzer using the waveguide method. The average electromagnetic shielding effectiveness was 37.11 dB. (3) The electromagnetic shielding effectiveness in the frequency range of 0.2~2.0 THz was tested using a terahertz time-domain spectroscopy (THz-TDS) system in transmission mode and reflection mode. The average electromagnetic shielding effectiveness was 46.68 dB.
[0030] The mechanical sensing performance test of the composite material is to use an electronic tensile testing machine to measure the stress-strain curve, and use an LCR tester to characterize the resistance change of the composite material during the stretching process. The tensile strain sensitivity of the composite material is measured to be 2673.
[0031] The Joule heating performance test of the composite material is carried out by monitoring the real-time temperature change of the composite material surface at room temperature using an infrared thermometer. It is measured that under a voltage of 10V and an action of 600 seconds, the average surface temperature of the composite material is 123°C. Example 4
[0032] (1) Carbon powder modification: Immerse carbon powder with an average particle size of 13 μm in an aqueous solution of 3-aminopropyltriethoxysilane with a mass percentage concentration of 5%, stir, heat to 40°C for reaction for 2 hours, filter, rinse with water, and dry to obtain modified carbon powder; (2) Catalytic activation: Place the modified carbon powder in a 3% by mass concentration of palladium chloride aqueous solution, stir at room temperature for 1 hour, filter, and then disperse the solid in a 3% by mass concentration of 2-aminopyridine aqueous solution, stir at room temperature for 1 hour, filter, rinse the solid with water, and dry to obtain activated carbon powder; (3) Chemical nickel plating: The activated carbon powder is placed in a chemical nickel plating solution, placed at 80°C for 3 minutes, taken out, rinsed with water, and dried to obtain nickel-coated carbon powder; wherein the components and concentrations of the chemical nickel plating solution are: NiCl 2 6H 2 O: 60 g / L, NaKC 4 H 4 O 6 :70g / L,NaH 2 PO 2 ·2H 2 O: 30g / L, NH 3 ·H 2 O: 50 g / L, the balance is deionized water; (4) Slurry preparation: Mix the nickel-coated carbon powder with a graphite conductive adhesive having a solid content of 4% and stir for 1 hour to obtain a composite slurry; wherein the mass ratio of the nickel-coated carbon powder to the graphite conductive adhesive is 0.08; (5) Coating and molding: prepare two square plastic molds with a height of 0.35 mm and a side length of 16 cm. First, pour the composite slurry into one mold and fill it up. Use a scraper to scrape off the excess composite slurry. Then, lay the modal cotton fabric cut into 15 cm × 15 cm flat on the slurry to ensure that the fabric is in full contact with the slurry. Then, place the second mold on the first mold and align the four sides. Then, pour the composite slurry on the modal cotton fabric in the mold and fill it up. Use a scraper to scrape off the excess composite slurry. Place it at room temperature for 24 hours, demold it, place it in an oven, heat it to 45°C, and keep it for 3 hours to obtain a flip-type multifunctional terahertz electromagnetic shielding composite material.
[0033] The electromagnetic shielding performance tests of the composite material are: (1) The electromagnetic shielding effectiveness in the frequency range of 0.3~3.0 GHz was tested by a vector network analyzer using the coaxial transmission line method. The average electromagnetic shielding effectiveness was 41.76 dB. (2) The electromagnetic shielding performance and S parameters in the frequency range of 8.2~12.4 GHz were tested by vector network analyzer using the waveguide method. The average electromagnetic shielding effectiveness was 38.11 dB. (3) The electromagnetic shielding effectiveness in the frequency range of 0.2~2.0 THz was tested using a terahertz time-domain spectroscopy (THz-TDS) system in transmission mode and reflection mode. The average electromagnetic shielding effectiveness was 47.12 dB.
[0034] The mechanical sensing performance test of the composite material is to use an electronic tensile testing machine to measure the stress-strain curve, and use an LCR tester to characterize the resistance change of the composite material during the stretching process. The tensile strain sensitivity of the composite material is measured to be 2752.
[0035] The Joule heating performance test of the composite material is carried out by monitoring the real-time temperature change of the composite material surface at room temperature using an infrared thermometer. It is measured that under a voltage of 10V and an action of 600 seconds, the average surface temperature of the composite material is 124°C. Example 5
[0036] (1) Carbon powder modification: Immerse carbon powder with an average particle size of 12 μm in an aqueous solution of 8% by mass concentration of 3-aminopropyltriethoxysilane, stir, heat to 35°C for reaction for 3 hours, filter, rinse with water, and dry to obtain modified carbon powder; (2) Catalytic activation: Place the modified carbon powder in a 2% by mass concentration of palladium chloride aqueous solution, stir at room temperature for 2 hours, filter, and then disperse the solid in a 2% by mass concentration of 2-aminopyridine aqueous solution, stir at room temperature for 2 hours, filter, rinse the solid with water, and dry to obtain activated carbon powder; (3) Chemical nickel plating: The activated carbon powder is placed in a chemical nickel plating solution, placed at 75°C for 4 minutes, taken out, rinsed with water, and dried to obtain nickel-coated carbon powder; wherein the components and concentrations of the chemical nickel plating solution are: NiCl 2 6H 2 O: 55 g / L, NaKC 4 H 4 O 6 :75 g / L,NaH 2 PO 2 ·2H 2 O: 28 g / L, NH 3 ·H 2 O: 55 g / L, the balance is deionized water; (4) Slurry preparation: Mix the nickel-coated carbon powder with a graphite conductive adhesive having a solid content of 3% and stir for 1.5 hours to obtain a composite slurry; wherein the mass ratio of the nickel-coated carbon powder to the graphite conductive adhesive is 0.05; (5) Coating and molding: prepare two square plastic molds with a height of 0.35 mm and a side length of 16 cm. First, pour the composite slurry into one mold and fill it up. Use a scraper to scrape off the excess composite slurry. Then, lay the modal cotton fabric cut into 15 cm × 15 cm flat on the slurry to ensure that the fabric is in full contact with the slurry. Then, place the second mold on the first mold and align the four sides. Then, pour the composite slurry on the modal cotton fabric in the mold and fill it up. Use a scraper to scrape off the excess composite slurry. Place it at room temperature for 24 hours, demold it, place it in an oven, heat it to 40°C, and keep it for 4 hours to obtain a flip-type multifunctional terahertz electromagnetic shielding composite material.
[0037] The electromagnetic shielding performance tests of the composite material are: (1) The electromagnetic shielding effectiveness in the frequency range of 0.3~3.0 GHz was tested by a vector network analyzer using the coaxial transmission line method. The average electromagnetic shielding effectiveness was 41.99 dB. (2) The electromagnetic shielding performance and S parameters in the frequency range of 8.2~12.4 GHz were tested by vector network analyzer using the waveguide method. The average electromagnetic shielding effectiveness was 38.30 dB. (3) The electromagnetic shielding effectiveness in the frequency range of 0.2~2.0 THz was tested using a terahertz time-domain spectroscopy (THz-TDS) system in transmission mode and reflection mode. The average electromagnetic shielding effectiveness was 47.13 dB.
[0038] The mechanical sensing performance test of the composite material is to use an electronic tensile testing machine to measure the stress-strain curve, and use an LCR tester to characterize the resistance change of the composite material during the stretching process. The tensile strain sensitivity of the composite material is measured to be 2813.
[0039] The Joule heating performance test of the composite material is carried out by monitoring the real-time temperature change of the composite material surface at room temperature using an infrared thermometer. It is measured that under a voltage of 10V and an action of 600 seconds, the average surface temperature of the composite material is 125°C.
Claims
1. A method for preparing a flip-type multifunctional terahertz electromagnetic shielding composite material, characterized in that: (1) Carbon powder modification: immerse carbon powder with an average particle size of 10-13 μm in an aqueous solution of 3-aminopropyltriethoxysilane with a mass percentage concentration of 5-10%, stir, heat to 30-40°C and react for 2-4 hours, filter, rinse with water, and dry to obtain modified carbon powder; (2) Catalytic activation: Place the modified carbon powder in a 1-3% mass percent palladium chloride aqueous solution, stir at room temperature for 1-3 hours, filter, and then disperse the solid in a 1-3% mass percent 2-aminopyridine aqueous solution, stir at room temperature for 1-3 hours, filter, rinse the solid with water, and dry to obtain activated carbon powder; (3) Chemical nickel plating: Place the activated carbon powder in a chemical nickel plating solution, place it at 70-80°C for 3-5 minutes, take it out, rinse it with water, and dry it to obtain nickel-coated carbon powder; wherein the components and concentrations in the chemical nickel plating solution are: NiCl2·6H2O: 50-60 g / L, NaKC4H4O6: 70-80 g / L, NaH2PO2·2H2O: 25-30 g / L, NH3·H2O: 50-60 g / L, and the balance is deionized water; (4) Slurry preparation: Mix the nickel-coated carbon powder with a graphite conductive adhesive having a solid content of 2-4%, and stir for 1-2 hours to obtain a composite slurry; wherein the mass ratio of the nickel-coated carbon powder to the graphite conductive adhesive is 0.01-0.10; (5) Coating and molding: prepare two square plastic molds with a height of 0.35 mm and a side length of 16 cm. First, pour the composite slurry into one mold and fill it up. Use a scraper to scrape off the excess composite slurry. Then, lay the modal cotton fabric cut into 15 cm × 15 cm flat on the slurry to ensure that the fabric is in full contact with the slurry. Then, place the second mold on the first mold and align the four sides. Then, pour the composite slurry on the modal cotton fabric in the mold and fill it up. Use a scraper to scrape off the excess composite slurry. Place it at room temperature for 24 hours, demold it, place it in an oven, heat it to 30~45℃, and keep it for 3~5 hours to obtain a flip-type multifunctional terahertz electromagnetic shielding composite material.
2. The flip-type multifunctional terahertz electromagnetic shielding composite material according to claim 1, characterized in that: The electromagnetic shielding performance tests of the flip-type multifunctional terahertz electromagnetic shielding composite material are: (1) The electromagnetic shielding effectiveness in the frequency range of 0.3~3.0 GHz was tested by a vector network analyzer using the coaxial transmission line method. The average electromagnetic shielding effectiveness was 41.65~42.88 dB. (2) The electromagnetic shielding performance and S parameters in the frequency range of 8.2~12.4 GHz were tested by vector network analyzer using the waveguide method. The average electromagnetic shielding effectiveness was 35.90~38.31 dB. (3) The electromagnetic shielding effectiveness in the frequency range of 0.2~2.0 THz was tested using a terahertz time-domain spectroscopy system in transmission mode and reflection mode. The average electromagnetic shielding effectiveness was 45.93~48.63 dB.
3. The flip-type multifunctional terahertz electromagnetic shielding composite material according to claim 1, characterized in that: The mechanical sensing performance test of the flip-type multifunctional terahertz electromagnetic shielding composite material is to use an electronic tensile testing machine to measure the stress-strain curve, and use an LCR tester to characterize the resistance change of the composite material during the stretching process. The tensile strain sensitivity of the composite material is measured to be 2500~2897.
4. The flip-type multifunctional terahertz electromagnetic shielding composite material according to claim 1, characterized in that: The Joule heating performance test of the flip-type multifunctional terahertz electromagnetic shielding composite material is carried out by using an infrared thermometer to test the real-time temperature change on the surface of the composite material at room temperature. It is measured that under a voltage of 10V and an action of 600 seconds, the average surface temperature of the composite material is 120~126℃.
Citation Information
Patent Citations
Application of polymer-carbon material for shielding from electromagnetic radiation with wavelengths in sub-terahertz and terahertz ranges
CN111630095A
A polymer-based electromagnetic shielding material with shielding effectiveness in the GHz to terahertz band, and its preparation method and application
CN117050370B